Wire coating in eccentric geometry with fluid and solid interaction using 3D simulation by CFD - Kriengkrai Nabudda; Ninart Booprempree; Wirote Ritthong; Kridtapas Cheyaksorn; Sontinan Intasonti; P. Poungthong (Case Studies in Thermal Engineering, 2025)
Wire coating processes are fundamental to the production of high-performance insulated wires, where precise regulation of resin flow and thermal behaviour is imperative to achieving uniform coatings. This study utilises three-dimensional (3D) computational fluid dynamics (CFD) simulations to investigate fluid-solid interactions in classical wire coating, with a particular emphasis on eccentric geometry. The findings indicate that increasing eccentricity induces pronounced asymmetries in flow dynamics, resulting in elevated shear stress, increased pressure drops, and non-uniform heat dissipation. These effects intensify temperature-dependent viscosity variations and heighten the risk of thermal degradation. Additionally, temperature-dependent density distributions become increasingly heterogeneous, leading to diminished thermal stability and reduced cooling efficiency. Specifically, at 20 % eccentricity, the minimum temperature decreases from 100.97 °C to 73.81 °C, while the minimum density declines from 814.15 kg/m 3 to 274.53 kg/m 3 , causing localised resin accumulation and depletion. Such variations compromise coating integrity and necessitate higher energy input for effective cooling. To mitigate these adverse effects, optimised flow regulation, precise temperature control, and advanced cooling strategies are essential. This study offers critical insights into wire coating dynamics, providing a framework for improving process efficiency, coating quality, and material utilisation in industrial applications.
Keywords: Lattice Boltzmann Simulation Studies; Fluid Dynamics and Vibration Analysis; Particle Dynamics in Fluid Flows